Financial Distress, Sales Growth, and Gender Diversity: Dampaknya pada Tax Aggressiveness (Studi pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2021-2023) - Ratu Zahra Pacita; Memen Suwandi; Namla Elfa Syariati (Academic Bright Collaboration, 2025)
This study aims to examine the effect of financial distress and sales growth on tax aggressiveness in basic and chemical sector companies listed on the IDX in 2021–2023, as well as to examine the role of gender diversity as a moderating variable. This study is quantitative with a comparative causal approach, using secondary data from www.idx.co.id. The sample consisted of 20 companies selected through purposive sampling. Data analysis was carried out using multiple linear regression and Moderating Regression Analysis (MRA). The results show that financial distress and sales growth have a negative effect on tax aggressiveness. Gender diversity cannot weaken the effect of financial distress on tax aggressiveness, but gender diversity can weaken the effect of sales growth on tax aggressiveness.